Comparing Aerial Lidar Observations With Terrestrial Lidar and Snow‐Probe Transects From NASA's 2017 SnowEx Campaign. Issue 7 (1st July 2019) - Currier, William Ryan; Pflug, Justin; Mazzotti, Giulia; Jonas, Tobias; Deems, Jeffrey S.; Bormann, Kat J.; Painter, Thomas H.; Hiemstra, Christopher A.; Gelvin, Arthur; Uhlmann, Zach; Spaete, Lucas; Glenn, Nancy F.; et al.
Abstract: NASA's 2017 SnowEx field campaign at Grand Mesa, CO, generated Airborne Laser Scans (ALS), Terrestrial Laser Scans (TLS), and snow‐probe transects, which allowed for a comparison between snow depth measurement techniques. At six locations, comparisons between gridded ALS and TLS observations, at 1‐m resolution, had a median snow depth difference of 5 cm, root‐mean‐square difference of 16 cm, mean‐absolute difference of 10 cm, and 3‐cm difference in standard deviation. ALS generally had greater but similar snow depth values to TLS, and results were not sensitive to the gridded cell size between 0.5 and 5 m. The greatest disagreements were where snow‐off TLS scans had shrubs and high incidence angles, leading to deeper snow depths (>10 cm) from ALS than TLS. The low vegetation and oblique angles caused occlusion in the TLS data and thus produced higher snow‐off bare Earth models relative to the ALS. Furthermore, in subcanopy areas where both ALS and TLS data existed, snow depth differences were comparable to differences in the open. Meanwhile, median values from 52 snow‐probe transects and near‐coincident ALS data had a mean difference of 6 cm, root‐mean‐square difference of 8 cm, mean‐absolute difference of 7 cm, and a mean difference in the standard deviation of 1 cm. Snow depth probes had greater but similar snow depth values to ALS. Therefore, based on comparisons with TLS and snow depth probes, ALS captured snow depth magnitude with better than or equal agreement to what has been reported in previous studies and showed the ability to capture high‐resolution spatial variability. Key Points: Snow depth magnitude and spatial variability derived from aerial lidar generally agreed with terrestrial lidar and snow‐probe transects Snow depth differences between aerial and terrestrial lidar underneath the canopy were comparable to differences in the open Largest differences between aerial and terrestrial lidar were in areas with shrubs and where terrestrial lidar incidence angles were high